Contextual Teaching and Learning Berbasis Ajaran Catur Guru Untuk Meningkatkan Aktivitas dan Prestasi Belajar Pendidikan Agama Hindu dan Budi Pekerti - Mastiningsih, Ni Nyoman; Sriasih, Ni Wayan (Prabha Vidya, 2024)
AbstrakThis research aims to increase learning activities and achievements in Hindu religious education and character in class IX students at Mutiara Singaraja Middle School, academic year 2023/2024 academic year through the application of the Contextual Teaching and Learning (CTL) model combined with teacher chess teachings to increase student activity and learning achievement of Hindu Religion and Character Education for Class IX of Mutiara Singaraja Middle School for the 2023/2024 Academic Year. This research is classroom action research carried out in two cycles consisting of planning, action implementation, observation, evaluation, analysis and reflection stages carried out in each cycle. The subjects of this research were class IX students at Mutiara Singaraja Middle School, in the even semester, totaling 16 students, consisting of 7 boys and 9 girls. Student activity data is collected using the observation method, while student learning achievement data is collected using the testing method in the form of objective tests in the form of multiple choices. The results of this research show that there was an increase in the learning activities of class IX students at Mutiara Singaraja Middle School in the Hindu Religion subject in cycle I with a score of 66.75%, while in cycle II with a score of 81%. So there is an increase in student activity in the learning process by 14.25%. For Student Learning Achievement, in cycle I the class average score was 77.81 with an Absorption Capacity of 77.81% and Learning Completeness 68.75%. Meanwhile in cycle II the average class was 82.5 with Absorption Capacity 82.5% and Learning Completeness 87.5%. So there is an increase in student learning achievement in the learning process by 18.75%. Based on the results of this research, it means that there has been an increase in student activity and learning achievement in class IX of Mutiara Singaraja Middle School. It is hoped that the (CTL) Contextual Teaching and Learning model combined with the Teachings and learning process to improve studend activity and learning achievement in Hinduism subjects and other subjects.